Dr. Noor Suraya produces EnviRoof for sustainable stormwater management - Nur Hartini, Mohd Hatta (2022)
PEKAN, 6 October 2022 – Cities continue to grow rapidly as migration from rural to urban areas increases. This increase indirectly causes various urbanisation or municipal issues to occur.